An architecture-based modelling of fault-tolerant SOA-based systems. (25th May 2023) - Goel, Swati
Service-oriented architecture (SOA) may effectively be implemented in distributed software development like cloud computing, internet of things, etc. Expectations from these systems, in terms of their reliability and availability, are increasing day by day. Fault-tolerance is an approach that ensures the correct functioning of the system even in the presence of faults. Various fault-tolerance mechanisms may be applied on a system. It is a cumbersome task to decide which mechanism is more suitable for a specific situation. Implementation of fault-tolerance involves as an additional cost factor due to the redundancy of software components. One has to intelligently decide what level of redundancy needs to be applied in a system. In this paper, a fault-tolerance policy, at an architectural level, is proposed for an SOA-based system. The proposed policy is based on the severity analysis of various software services in an SOA-based system. Architecture analysis and design language (AADL) is used for the modelling of the system. Fault tree analysis and functional hazard assessment have been used for severity analysis. A 'smart home security system (SHSS) ' is used for the demonstration of the practicality of the proposed model. The proposed policy can be used as a fault-tolerance solution.